PREFERENSI KONSUMEN TERHADAP PRODUK HASIL LAUT (STUDI KASUS RESTORAN SEAFOOD MJM KOTA PALU, SULAWESI TENGAH) - Mohamad Gazali (JURNAL PERIKANAN TROPIS, 2016)
Many bussinessman develop the restaurant of seafood in the Palu Town, Central Sulawesi. The production’s fisheries activities yielded high protein products and consumed by community, not only limited to fisheries products but also the processed product with various taste. One of the products of fisheries that distributed in the market were the marine products in The Palu town. The objectives of this study is to analyse the preferences of consumer on the marine products in the Palu town. The study method is the case study (case study with a unit of famous seafood restaurant cases  MJM that located in the Palu town. The sampling method which used in this study was accidental sampling. The type of fisheries product that sold in the Seafood Restaurant of MJM were groupers, snapper fish, baronang, katamba, mangrove’s crabs, shrimps and squid. The interest of marine product was undertaken with analysis of multiple linear regression and yielded F-count > F-Table with level of significance 95% shown concordance of consumer’s interest to attribute of  product. Simultanously, attribute of  product of diversity (X1) = , quality (X2), price (X3), taste (X4), and service (X5) have influenced significantly to preference of consumer whereas partially, the product attribute of quality (X2) possess effect the most dominant with coefficient of  regression value is 0,531 or 53,1%. Thus, the preference of consumer to marine product is quality of fish was level of freshing quality, clean, consumed healthty.